1994
DOI: 10.1123/pes.6.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Capacity and Grade-Walking Economy of Children 5–9 Years Old: A Longitudinal Study

Abstract: Maximal oxygen uptake (VO2max), submaximal grade-walking oxygen uptake, and anthropometric measures were measured in a group of 19 children in 1988 and in 1992. The children were 5.2 ± .9 years old in 1988 and 9.2 ± 1.0 in 1992. The VO2max did not change relative to body weight over the 4 years (44.6 ml·kg−1·min−1 in 1988 versus 43.3 ml·kg−1·min−1 in 1992). Lower specific weight-relative oxygen uptakes were seen at the submaximal work levels in 1992 than in 1988, indicating an improvement in grade-walking econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Anthropometric factors such as height, weight and body fat have been shown to impact energy consumption [27,28]. Allometric scaling is employed to reduce or even remove the impact of key anthropometric and physiological variables on the energy variables, this is important when comparing the energy cost of walking in children of different ages and body morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Anthropometric factors such as height, weight and body fat have been shown to impact energy consumption [27,28]. Allometric scaling is employed to reduce or even remove the impact of key anthropometric and physiological variables on the energy variables, this is important when comparing the energy cost of walking in children of different ages and body morphology.…”
Section: Discussionmentioning
confidence: 99%
“…This methodological problem might" be the reason why these low values have not been confirmed. For example Shuleva et al (1990) reported values of 44.5 mL-kg-'-mnr 1 in 3 to 4-year-old children, Houlsby (1986) 33.8 mL-kg-'-min' 1 in 5-year-old children and Forster et al (1994) 44.6 mL-kg-'-mhr 1 in children aged 5.2 ± 0.9 years. Besides any methodological problems, the aforementioned disadvantage in providing oxygen for working muscles may be differently expressed in various children.…”
Section: Oxygen Transport Systemmentioning
confidence: 96%
“…The ef®ciency factor may be important in children since ef®ciency is known to improve during maturation. 25 The ®nding that time devoted to physical activity is more important than the combined energy cost implies that long bouts of physical activity (which can be sustained at low intensity) may be more protective than shorter bouts of high intensity activity. These two scenarios may have the same energy cost, but extended periods of low intensity exercise may be more bene®cial because of the promotion of an active lifestyle and the avoidance of a sedentary lifestyle that has been implicated to promote food intake, especially snacking.…”
Section: Discussionmentioning
confidence: 99%
“…Second, activity energy expenditure in children is in¯uenced by ef®ciency which improves during childhood growth. 25 We did not perform any measure of ef®ciency in this study but the lack of relationship between fat mass and activity energy expenditure remained apparent after adjusting for fat free mass and age (which may be proxy measures of the development change in ef®ciency). The third possible explanation is that activity energy expenditure may be an imprecise measure.…”
Section: Discussionmentioning
confidence: 99%